PERUBAHAN pH , KEASAMAN DAN INDEKS FERMENTASI BIJI KAKAO SELAMA FERMENTASI HASIL BIJI KAKAO (THEOBROMA CACAO) - Apriyanto, Mulono (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2017)
Most cocoa beans are produced by farmers Indonesia is dry cocoa drying whose quality can be improved by the fermentation method, but it takes more optimization for fermentation can run well. This study aimed to determine changes in the chemical properties of fermented dry cocoa beans drying. Dry beans drying is obtained by drying the wet cocoa beans (fresh) in a cabinet dryer with a previously conditioned at a temperature such as drying in the sun, and each determined the reduction of sugar levels. Experiments fermented dry cocoa beans are fermented in the fermentation container with the amount of 100 grams of seed per container. Before the first fermented dry cocoa beans drying on rehydration to obtain a moisture content approaching fresh beans, dry beans drying then incubated for six days and without inverted during fermentation. Each treatment was repeated three times and observed every 24 hours to 120 hours. Reduction sugar, acid levels tertitrasi, the population of yeasts and acetic acid bacteria in fermented pulp was observed during the fermentation process. To determine the quality of dry beans drying measurement of pH and the fermentation index during fermentation.